Fabrication Of 50 µm transistor and AlNiAu interconnection process - Shaffie Husin (Universiti Malaysia Perlis, 2008)
Generally process fabrication transistor will starts by cleaning the wafer, formation region drain, D and source, S, get oxide and deposited aluminum as contact with the source, drain and gate. Mask is very important thing to develop the pattern transfer in fabrication process Based on that, the project fabrication transistor not successful because quality of mask not very compatible to develop the smaller size. AlNiAu as the interconnection involved of several steps. It starts with Al deposition, the follow by cleaning, activation and zincation to remove the oxide layer thus, provide good adhesive. The next process is nickel deposition and lastly gold in deposited on top of Ni. Gold is used because of is not easily oxidize upon exposure for environment. Size of bond pad, chemical and temperature during the process and most important is thickness of aluminum, passivation and also photoresist layer, must be determined to achieve consistent result.